Smart City Applications with Solutions – A Survey - Ashwin, M.; Vasantha, Bhavani; Roshini, A.; Kumar Anguraj, Dinesh (International Journal of Psychosocial Rehabilitation, 2019)
A smart city utilizes information and communications technology (ICT) to improve its livability, workability, and sustainability. The problems with smart cities are lack of financing, ICT, integrated services, citizen management, and Smart City Visionary. To overcome the smart city problem, it utilizes the ICT technology to enhance livability, workability, and sustainability. The smart city applications are smart buildings, smart energy, smart utilities, smart administration, smart enterprises, smart transportation, smart security, smart retail, smart agriculture, etc. This study investigates smart city applications with solutions.